Structural and electrochemical properties of dense yttria-doped barium zirconate prepared by solid-state reactive sintering - Yun, Dae Sik; Kim, Jaegyeom; Kim, Seung Joo; Lee, Jong Heun; Kim, Jong Nam; Yoon, Hyung Chul; Yu, Ji Haeng; Kwak, Minseok; Yoon, Hana; Cho, Younghyun; Yoo, Chung Yul (Energies, 2018)
For practical utilization of proton-conducting ceramic fuel cells and electrolyzers, it is essential to lower the sintering temperature and processing time of BaZrO3-based proton conductors. We investigated the effect of sintering temperature and time on the structural and electrochemical properties of dense BaZr0.8Y0.2O3 (BZY) prepared by a solid-state reactive sintering process, using NiO as a sintering aid. The sintered BZY prepared from the micronized precursor powder exhibited a density higher than 93%, and an average grain size in the range of 0.6 to 1.4 μm. The orthorhombic BaY2NiO5 phase was also observed in the sintered BZY from the combined conventional and synchrotron X-ray diffraction measurements. Electrochemical impedance spectroscopy showed that the total proton conductivities of BZY can be modulated by sintering temperature in a wet reducing atmosphere. The maximum total ion transport number achieved was 0.89 at 600 °C, and the maximum power density of the symmetric BZY electrolyte supported cell with Pt electrodes was 5.24 mWcm-2 at 900 °C.
Keywords: BaZrO3; Electrolyte-supported cells; Proton conducting ceramic; Proton-conducting oxides; Reactive sintering; Sintering temperature and time; Sintering temperatures; Synchrotron x ray diffraction; BaZrO3; Electrochemical properties; Proton-conducting oxides; Solid-state reactive sintering